Diagnóstico comunitario de salud del barrio Esmeralda norte sector II, septiembre-diciembre del 2013 - Hidalgo Ochoa, Jhulina Elizabeth (2014)
The present investigation has as main objective to Contribute the invigoration of the PATTERN OF INTEGRAL ATTENTION OF THE COMMUNITY NATIONAL SYSTEM OF FAMILY HEALTH AND INTERCULTURAL in the University Hospital of Motupe, contributing with statistical and data that will allow to the Basic Teams of Health - EAIS (Teams of Integral Attention of Health) to formulate local proposals of health, spread to improve the quality of life of the community of Esmeralda Norte Sector II. The universe consisted of 77 families and 304 inhabitants, this research is descriptive, in which facts and characteristics related to population and environment are detailed, the instrument for data collection was the family record compiled by the MSP and an annex to this record, the interview form complemented the information, the data is also analyzed, obtaining results that will serve as a base line. Among the most relevant data include: that the most prevalent sex is female, the level of outstanding education is High School, 2 Illiterate one of which corresponds to the head of the family was found, children were not identified with outline incomplete immunization or nutrition problems as schoolchildren and adolescents all have good nutritional status and most studies in regard to sexually active women, the rhythm method is the most widely used family planning. Regarding the epidemiological profile include the Hypertension is the most prevalent chronic disease affecting aged 20 to 64 years and 65 years and over, degenerative diseases found among colon cancer , and disabilities regarding the outstanding are the physical and intellectual disabilities. Research bibliography and appendices which involves the development of it is supported. Keywords: Community health diagnosis the Barrio Esmeralda Norte Sector II and its results.